Analysis of items on test instruments of mathematical representation ability on quadrilateral material for junior high school student - A Nurainy; D Darhim; J A Dahlan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This article presents about test instruments to measure students' mathematical representation abilities. The development of this instrument is one of several research steps undertaken by the author.A good test instrument must meet the valid and reliable criteria.The steps of developing this mathematical representation instrument include:(1) study of mathematical representation literature; (2) create a lattice based on indicators of mathematical representation ability; (3) preparation of test items; (4) trials; (5) analysis of trial results; (6) revisions; (7) retest; And (8) analysis of retesting results.The instrument was tried to 30 grade VIII students from one of the junior high school in Tangerang.Based on the analysis of the results obtained nine items test math representation abilities are valid and have high reliability.Thus, the instrument can be used to collect research data that measures students' mathematical representation abilities.